2014
DOI: 10.1210/en.2014-1260
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of GLUT Transporters by Flavonoids in Androgen-Sensitive and -Insensitive Prostate Cancer Cells

Abstract: Cancer cells show different metabolic requirements from normal cells. In prostate cancer, particularly, glycolytic metabolism differs in androgen-responsive and nonresponsive cells. In addition, some natural compounds with antiproliferative activities are able to modify glucose entry into cells by either modulating glucose transporter (GLUT) expression or by altering glucose binding. The aim of this work was to study the regulation of some GLUTs (GLUT1 and GLUT4) in both androgen-sensitive (LNCaP) and -insensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 54 publications
2
63
0
Order By: Relevance
“…62 This overexpression seems to be dependent on hypoxia more than androgenic regulation. 64 Regarding its intracellular localization, GLUT1 was also found in the Golgi apparatus where it could have a role in supplying glucose to the prostatic fluid. 24 Furthermore, GLUT1 is involved in the increase in glucose uptake by inflammatory cells in PCa, 63 and it was recently described that this isoform overexpression in PCa might be mediated by the reduced levels of microRNA-132.…”
Section: Glut Transporters As Clinical Targets In Pcamentioning
confidence: 99%
See 1 more Smart Citation
“…62 This overexpression seems to be dependent on hypoxia more than androgenic regulation. 64 Regarding its intracellular localization, GLUT1 was also found in the Golgi apparatus where it could have a role in supplying glucose to the prostatic fluid. 24 Furthermore, GLUT1 is involved in the increase in glucose uptake by inflammatory cells in PCa, 63 and it was recently described that this isoform overexpression in PCa might be mediated by the reduced levels of microRNA-132.…”
Section: Glut Transporters As Clinical Targets In Pcamentioning
confidence: 99%
“…24 Furthermore, GLUT1 is involved in the increase in glucose uptake by inflammatory cells in PCa, 63 and it was recently described that this isoform overexpression in PCa might be mediated by the reduced levels of microRNA-132. 64 Regarding its intracellular localization, GLUT1 was also found in the Golgi apparatus where it could have a role in supplying glucose to the prostatic fluid. 65 On the other hand, GLUT3 is activated via caveolin-1 in AR-negative cells 66 and GLUT12, which is also considered an insulin-dependent transporter, was found in PCa but not in non-tumor samples, 65 suggesting a similar role than other insulin-dependent transporters, such as GLUT4, in tumorigenesis.…”
Section: Glut Transporters As Clinical Targets In Pcamentioning
confidence: 99%
“…The glucose moiety in oleuropein may facilitate its diffusion into these cells in precedence to normal cells and therefore result in a greater inhibitory effect on cancer versus normal cells. Another study has indicated that the olive flavonoid apigenin is able to reduce the expression of GLUT1 in prostate cancer cell lines thereby inhibiting proliferation of the cancer [29]. …”
Section: Bioavailability Of Olive Leaf Polyphenolsmentioning
confidence: 99%
“…The addition of leaves increase the phenolic and chlorophyll content of the oil but also the organoleptic traits as measured in volunteer taste tests [24]. Components of OLE that are not detected in the oil from the fruit include several flavonoids, namely luteolin and apigenin, which have demonstrated anti-cancer properties [25,26,27,28,29]. In addition, the structure of phenolics differs between the olive fruit and leaf, with OLE containing a higher proportion with a glycoside moiety (Figure 2 and Table 1) [19].…”
Section: Introductionmentioning
confidence: 99%
“…The flavanoids genistein, phloretin, apigenin, and daidzein have different effects on reducing GLUT1 expression and glucose uptake in androgen responsive versus non-responsive prostate cancer cells and therefore different effects on reducing cell growth [128].…”
Section: F]fdg Is Therefore An Excellentmentioning
confidence: 99%